2022
DOI: 10.3390/ijerph19063424
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of the Factors Associated with Distress in Elderly Cancer Patients: A Systematic Review

Abstract: This study presents a systematic review of the sociodemographic, clinical, and psychosocial factors associated with distress in elderly cancer patients. Relevant studies were identified using four electronic databases: PubMed, Scopus, Web of Science and ProQuest. Cross-sectional and longitudinal studies exploring factors associated with distress in people over 60 years of age were included and independently assessed using the Joanna Briggs Institute Critical Assessment Checklists. A total of 20 studies met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Our finding regarding mental QOL may indicate survivors had fewer worries, fears, and distress related to concerns about disease recurrence or new cancer due to their age or the further they got from their cancer diagnosis 44‐46 . Also, the mental QOL finding may indicate that, in general, the survivors in our study had less physical, psychosocial, residential area disadvantage, better coping skills, more experience with chronic illness, positive spiritual and religious coping, higher resilience, social connectedness, or good social support and perspective of illness, and protective effects of being married, which could have mitigated the influence of LSM on their mental health 7,42,47,48,49,50,51,52,53,54,55,56 …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our finding regarding mental QOL may indicate survivors had fewer worries, fears, and distress related to concerns about disease recurrence or new cancer due to their age or the further they got from their cancer diagnosis 44‐46 . Also, the mental QOL finding may indicate that, in general, the survivors in our study had less physical, psychosocial, residential area disadvantage, better coping skills, more experience with chronic illness, positive spiritual and religious coping, higher resilience, social connectedness, or good social support and perspective of illness, and protective effects of being married, which could have mitigated the influence of LSM on their mental health 7,42,47,48,49,50,51,52,53,54,55,56 …”
Section: Discussionmentioning
confidence: 64%
“…[44][45][46] Also, the mental QOL finding may indicate that, in general, the survivors in our study had less physical, psychosocial, residential area disadvantage, better coping skills, more experience with chronic illness, positive spiritual and religious coping, higher resilience, social connectedness, or good social support and perspective of illness, and protective effects of being married, which could have mitigated the influence of LSM on their mental health. 7,42,47,48,49,50,51,52,53,54,55,56 To avoid or mitigate the negative consequences related to restricted LSM in older cancer survivors, it is important for healthcare providers to assess LSM routinely and intervene to address modifiable factors that may negatively impact LSM. Interventional strategies to address these modifiable factors impacting the individual's LSM need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, women with anxiety symptoms were almost 15-times more likely to have depressive symptoms compared with those without anxiety symptoms; as such, women diagnosed with BC could benefit from routine screening to rule out pre-existing psychological morbidity 30. The prevalence of depressive symptoms was also more frequent among women who had been diagnosed with BC at more advanced stages; this is likely as a result of awareness of their poorer prognosis compared with patients who are diagnosed at an earlier stage 31. A study conducted in Greece similarly found that women diagnosed with stage IV BC were 1.9-times more likely to experience depressive symptoms compared with patients diagnosed with stages I or II BC 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, older people with BC in Germany were found to be 1.2-times more likely to experience both depressive and anxiety symptoms compared with younger patients 37. In general, older individuals with BC may be more likely to report depressive symptoms compared with younger individuals because of lack of energy, increased sleep disturbances, decreased interest in activity and the coexistence of other conditions, such as cardiovascular disease, stroke, diabetes and hearing or visual impairments, all of which are more frequent in older age 31 35…”
Section: Discussionmentioning
confidence: 99%
“…Disease-related knowledge: a self-made questionnaire on disease-related knowledge was developed with reference to the literature [ 6 ], which contained the significance of tumor marker detection, the significance of positive results, examination precautions, the significance of return visit, and the importance of return visit, etc., with a total score of 100 points, indicating that the physical examinees had a better disease-related cognition level. Compliance behavior [ 7 ]: after the intervention, the compliance behavior such as regular return visit, reasonable diet, appropriate exercise, and regular routines of the two groups of physical examinees were evaluated, respectively, and the evaluation dimensions were complete compliance, partial compliance, and complete noncompliance, those who met complete and partial compliance were regarded as compliance, and those who met complete noncompliance were regarded as noncompliance, and the compliance rate of the two groups of physical examinees was compared.…”
Section: Methodsmentioning
confidence: 99%